Cogeneration potential study in food industry - Kannan, K. S.; Ab. Wahab, Abas; Abdullah, Haryati; Abdul Latif, Zulkarnain; Hassan, Mohamad Yusri (Universiti Teknologi Malaysia, 1998)
The increase in energy cost in recent years has created a situation where it has become essential to develop alternative energy technologies. Energy efficiency does not only mean reducing environmental degradation and increasing sustainability but also cost savings. Most energy managers employ common solutions to reduce plant inefficiencies in Malaysia such as "Energy Auditing", equipment replacement etc. One other energy efficient system is Cogeneration. Cogeneration can be considered as one of the many indications of progress in a healthy and efficient industrial growth. Cogeneration enables an industry to be not totally dependent on the utility supply but become inter-dependent and hence increasing availability. A well-planned cogeneration system can create a situation where plant operation need not be affected by utility blackouts; i.e. minimum production capacity is maintained. The Malaysian energy environment is a dynamic growth, where present excess capacity is projected to be fully utilised by the end of the century. The increasing demand for electricity is not evenly distributed in Malaysia and this off balance cause overloading in some areas. By cogenerating, the demand can be reduced and therefore the load on Tenaga Nasional Berhad or TNB transmission lines will also reduce. This would allow TNB to react to load f luctuation more effectively. Cogeneration will be a catalyst for the local natural gas industry since most industrial cogenerators (between 1MW to 10 MW) will be utilising natural gas as fuel source for gas engines and gas turbines. Cogeneration will also displace the need to build expensive power plants, which will mean eliminating transmission and distribution losses. Cogeneration will benefit the environment by reducing emissions, improve the use of natural resources, introduce better grid management, provide savings in Ringgit Malaysia, increase efficiency, added reliability and generating growth in the gas industry. The objective of this project was to evaluate the technical and economics viability of cogenerating in Malaysia. Two case studies were selected and evaluated. It was found that the lack of firm regulations and gas prices are the main factors discouraging cogeneration in Malaysia. Local industries were also found to be lacking in commitment towards cogenerating and efficient energy use. This thesis has forwarded recommendations and suggestions that will be required to improve the cogeneration scenario in Malaysia.